2020
DOI: 10.3390/jcm9082494
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Reverted the All-trans Retinoic Acid-Induced Cellular Proliferation of T24 Bladder Cancer Cell Line

Abstract: The treatment of solid cancers with pharmacological all-trans retinoic acid (ATRA) concentrations, even if it is a gold standard therapy for the acute promyelocytic leukaemia (APL), is not always effective due to some resistance mechanisms. Here the resistance to ATRA treatment of T24 cell line, bladder cancer, was investigated. T24 was not only resistant to cell death when treated at concentrations up to 20 µM of ATRA, but it was also able to stimulate the cellular proliferation. An over-expression of the fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Enrichment of proteins by lncDBET between lncDBET probe-treated cells and control probe-treated cells was presented, and 8 candidates (HRNR, POF1B, ALOX12B, FABP5, FLG, SBSN, PRDX2, HAL) were identified as potential lncDBET targets (|FC| ≥ 2, P < 0.05) (Figure 5 B). Taking FC and binding score ( Table S5 ), KEGG pathway analysis (Figure 5 C) and association with human cancers into account as screening standards 26 , only the PPAR signaling pathway was related to BCa, and thus, only FABP5 was selected for further verification. In addition, the peptide sequence of FABP5 “LVVECVMNNVTCTR” was identified (Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment of proteins by lncDBET between lncDBET probe-treated cells and control probe-treated cells was presented, and 8 candidates (HRNR, POF1B, ALOX12B, FABP5, FLG, SBSN, PRDX2, HAL) were identified as potential lncDBET targets (|FC| ≥ 2, P < 0.05) (Figure 5 B). Taking FC and binding score ( Table S5 ), KEGG pathway analysis (Figure 5 C) and association with human cancers into account as screening standards 26 , only the PPAR signaling pathway was related to BCa, and thus, only FABP5 was selected for further verification. In addition, the peptide sequence of FABP5 “LVVECVMNNVTCTR” was identified (Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…The role of retinoic acid in bladder cancers remains under investigation. In vitro studies show variable effects of retinoids in different bladder cancer cells [ 19 , 21 , 22 ], with no studies dedicated to the effects of retinoids on a specific molecular subtype of bladder cancer, including basal muscle-invasive bladder cancer. The effect of retinoids needs to be investigated in each subtype of bladder cancer to determine if there is an avenue for precision therapy in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid (all-trans retinoic acid (ATRA), tretinoin) is an active metabolite of vitamin A that can modify both the retinoic acid receptor (RAR) and the retinoid X receptor (RXR) [ 18 ]. In vitro studies have shown variable effects of retinoids on bladder cancer cell lines (T24, RT4, 5637, RT112, and HT-1376 cells), ranging from a cytostatic effect, stimulation of proliferation, and inhibition of EGF-stimulated cell proliferation to direct activation of PPARγ [ 19 , 20 , 21 , 22 ]. In vivo studies have been limited, primarily focusing on the effect of dietary vitamin A in preventing bladder cancer development [ 16 ], with scarce data available on the effect of retinoids on bladder cancer xenografts in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Different retinoids induced the expression of different nuclear retinoid receptors ( RARα , RARβ , RARγ ) and differentially altered the expression of apoptosis-associated genes ( p53 , GADD45 , bcl-2 , casp3 ) [ 74 , 88 ]. Moreover, it was shown that ATRA treatment was not always effective due to some resistance mechanisms and that ATRA could even induce a dose- and time-dependent cell proliferation [ 86 ]. A similar effect was also shown for bexarotene (also known as LGD1069 or Ro 26-445, brand name Targretin), which increased the incidence and size of tumours that developed in the BBN model [ 90 ].…”
Section: Experimental Models Of Bladder Cancer Play a Key Role In mentioning
confidence: 99%
“…The pharmacological use of retinoids encounters several limitations, such as the low concentrations of retinoids at the tumour site, short half-life, poor water solubility, susceptibility to light, heat, and oxidants, and rapid degradation during digestion resulting in low bioavailability and bioaccessibility [ 20 , 86 ]. One of the ways to increase retinoid plasma levels is to combine retinoid treatment with agents that inhibit retinoid degradation, which was tested in a BC clinical trial.…”
Section: Clinical Trials Of Retinoids For Chemoprevention and Treamentioning
confidence: 99%